Flash-Aware Page Replacement Algorithm. (12th August 2014) - Xu, Guangxia; Ren, Lingling; Liu, Yanbing
Abstract : Due to the limited main memory resource of consumer electronics equipped with NAND flash memory as storage device, an efficient page replacement algorithm called FAPRA is proposed for NAND flash memory in the light of its inherent characteristics. FAPRA introduces an efficient victim page selection scheme taking into account the benefit-to-cost ratio for evicting each victim page candidate and the combined recency and frequency value, as well as the erase count of the block to which each page belongs. Since the dirty victim page often contains clean data that exist in both the main memory and the NAND flash memory based storage device, FAPRA only writes the dirty data within the victim page back to the NAND flash memory based storage device in order to reduce the redundant write operations. We conduct a series of trace-driven simulations and experimental results show that our proposed FAPRA algorithm outperforms the state-of-the-art algorithms in terms of page hit ratio, the number of write operations, runtime, and the degree of wear leveling.